Use the tables to answer the question.

When trying to solve the quadratic equation x2+4x−5=7
, Jamal and George each provided their work in the tables.

Jamal

Step 1: Set equation = 0 x2+4x−12=0

Step 2: Write quadratic equation as the product of two factors (x+6)(x−2)=0

Step 3: Set each factor equal to 0 x+6=0 and x−2=0

Step 4: Solve each equation x=−6 and x=2



George

Step 1: Set equation = 0 x2+4x−5=7

Step 2: Write quadratic equation as the product of two factors (x+5)(x−1)=7

Step 3: Set each factor equal to 0 x+5=0 and x−1=0

Step 4: Solve each equation x=−5 and x=1

Which student is incorrect? Explain how you know that his solution is inaccurate.

(2 points)
0 / 10000 Word Limit
Skip to navigation

1 answer

To determine which student is incorrect, we need to analyze the steps taken by both Jamal and George in solving the quadratic equation \( x^2 + 4x - 5 = 7 \).

Step 1: Set the Equation to Zero

Initially, we need to move all terms to one side of the equation to set it equal to zero. Starting with \( x^2 + 4x - 5 = 7 \):

\[ x^2 + 4x - 5 - 7 = 0 \]

This simplifies to:

\[ x^2 + 4x - 12 = 0 \]

Both Jamal and George correctly set the equation to zero in Step 1.

Step 2: Factor the Quadratic Equation

Now let's look at the factoring of the quadratic \( x^2 + 4x - 12 \).

Jamal's factors: Jamal factored the equation as:

\[ (x + 6)(x - 2) = 0 \]

George's factors: George factored the equation as:

\[ (x + 5)(x - 1) = 7 \]

Here, George's factorization is incorrect for the equation \( x^2 + 4x - 12 = 0 \) because \( (x + 5)(x - 1) \) does not equal \( x^2 + 4x - 12 \).

Step 3: Setting Each Factor to Zero

Jamal set each factor correctly equal to 0:

\[ x + 6 = 0 \quad \Rightarrow \quad x = -6 \] \[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \]

George's equations are based on his incorrect factorization:

\[ x + 5 = 0 \quad \Rightarrow \quad x = -5 \] \[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \]

Conclusion

Jamal is correct, and his solutions are \( x = -6 \) and \( x = 2\).

George is incorrect because his factorization \( (x + 5)(x - 1) \) does not yield \( x^2 + 4x - 12 = 0 \). The correct factors should lead to a factoring that satisfies the original quadratic equation correctly, and hence George's solutions of \( x = -5 \) and \( x = 1 \) are also incorrect.

Therefore, George is the student who is incorrect.

Similar Questions
  1. Use the tables to answer the question.When trying to solve the quadratic equation x2+4x−5=7 , Jamal and George each provided
    1. answers icon 1 answer
  2. Use the tables to answer the question.When trying to solve the quadratic equation x2+4x−5=7 , Jamal and George each provided
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 2 answers
more similar questions